PENGELOLAAN BIAYA LINGKUNGAN DALAM UPAYA PENGHEMATAN BIAYA PADA PETERNAKAN AYAM “ABC” DI SUKOREJO - Farida, Khilda (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
This study aims to provide an alternative solution and how the role of the Environmental Cost Management in a Business Entity produce information that is able to identify, minimize, and manage environmental costs. This case study used a qualitative approach with a method of semi-structured interviews, document analysis, and field observations in poultry. The result of this study indicate that environmental cost management is very supportive in cost savings. Costs can be reduced if adverse environmental impacts can be minimized. With the method of Environmental Cost Management breeders can identify internal and external failures and manage it to minimize the total environmental cost by increasing prevention and detection activities.